THE EFFECT OF WORK DISCIPLINE AND WORK ENVIRONMENT ON THE PERFORMANCE OF MBKM STUDENTS' INTERNSHIP WITH WORK MOTIVATION AS AN INTERVENING VARIABLE - Juliana Ariska; Khairawati; Ibrahim Qamarius; Sullaida (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the influence of work discipline and work environment on the internship performance of students in the Merdeka Belajar Kampus Merdeka (MBKM) program, with work motivation as a mediating variable. The research was conducted on students participating in the Certified Internship and Independent Study Program (MSIB) at PT Bank BTPN Syariah Tbk. A quantitative approach was applied by distributing questionnaires to 222 respondents who had completed their internship. The data were analyzed using the Partial Least Square (PLS) method. The results indicate that work discipline and work environment positively and significantly influence work motivation, and that work motivation significantly influences internship performance. Additionally, work motivation is proven to mediate the relationship between work discipline and work environment on students' internship performance. This research is expected to contribute to the development of internship programs in both education and industry.